THE INFLUENCE OF THE QUALITY OF PRODUCTS AND PROMOTIONAL PRICES ON PURCHASING DECISIONS (STUDIES TAM-TAM BEVERAGE BUSINESS IN THE TAVERN STUDENT HARAPAN MEDAN) - Pratama, Arief chandra (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2025)
Competition today’s business world runs very fast, this encourages employers compete with each other in order to satisfy the needs of consumers by producing goods and services in accordance with the wishes of consumers. This study was conducted to determine yhe effect of product quality, price and promotional on purchase decisions in business Tam-Tams drink in the tavern students practice Harapan Medan. Both partially and simultaneously. This type of reasearch is the study of associative. With a sample of 100 people from the consumer population growing beverage Tam-Tams. The sampling technique used purposive sampling with multiple linier reference analytical techniques. Results from the study showed the product quality influence on purchase decisions in the beverage business Tam-Tams. Price influence on purchase decisions in the beverage business Tam-Tams. Promotions influence on purchase decisions in the beverage business Tam-Tams. In addition the results of this study indicate that the product quality and promotional price influence on purchase decisions in the beverage business Tam-Tams. Product quality and price promotion simultaneouslyhave the effectof 54,8% and the remaining 45,2% is influenced by other variabels that are not addressed in this study.